FAKTOR-YANG-BERHUBUNGAN-DENGAN-STRES KERJA-PADA-PEKERJA PENANGANAN PRASARANA DAN-SARANA UMUM JAKARTA BARAT (Studi Kasus di KeIurahan Pinangsia dan KeIurahan Krukut Jakarta Barat) - Vini Nur Puri Handayani; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Handling Infrastructure and Public Facilities or abbreviated as PPSU is work that needs to be done immediately and cannot be delayed. PPSU’s work includes handling waste problem and repairing public facilities. Many complex work and environmental responsibilities can cause work stress. The purpose of this study was to analyze the factors that related with work stress. This research used explanatory research method with quantitative method and cross sectional designs study. The population in this study were 98 workers at Pinangsia and 48 workers at Krukut. The samples from the Lemeshow formula were obtained by 49 workers at Pinangsia and 33 workers at Krukut. The instruments of this research were manual of HARS and research questionnaire. Results of research indicated there is 67,1% of workers deal with mild work stress. Data analysis used Chi Square test and Spearman Rank test to see the factors of work stress with the incidence of work stress in PPSU workers. The test showed there was a relationship between the variables of the relationship in work (p = 0,021) and social decisions (p = 0,013) with work stress. To minimize work stress, company can make refreshing activities can be carried out routinely such as outbound or recreational and eating together.